Methods of wintering steer calves that are to be grazed a full season and sold off grass. - Smith, E.F.; Baker, F.H.; Cox, R.F.; Good, D.L.; Holland, L.A. (Kansas Agricultural Experiment Station, 2012)
Four lots of 10 Hereford steer calves per lot were used in the study. The calves were part of 220 purchased from the Brite Ranch at Marfa, Texas. They cost 29 cents a pound delivered to Manhattan November 3, 1952. From the date received until they were placed on test December 18, 1952, they were fed prairie hay and 1 pound of soybean pellets per head daily. All lots were wintered on dry bluestem pasture except Lot 1 wintered in a drylot. The calves on pasture were rotated every 15 days to equalize any differences due to pasture. The pastures in which the steers grazed were stocked at a normal rate during the 1952 summer season; sufficient grass remained for winter grazing. The winter stocking rate ranged from 4 to 13 acres per steer, varying with the different sizes of pasture.
Keywords: Beef; Stocking rate; Gain; Protein